(403) Lecture Notes on Index Number ملاحظات حول أرقام المؤشرات - Van Rees, c. J. (The Institute of National Planning, 2025)
The work entitled “Lecture Notes on Index Numbers” addresses the concept of index numbers as one of the most important statistical and economic tools used to measure relative changes in economic and social phenomena over time. The significance of index numbers lies in their ability to simplify complex quantitative information and transform it into measurable indicators that facilitate comparisons and improve understanding of trends in prices, production, wages, income, and standards of living. The study focuses on the theoretical foundations of constructing index numbers and explains the methodological principles involved in selecting a base year and assigning relative weights to variables. It also reviews the major types of index numbers, including simple and weighted indices, together with the mathematical formulations commonly used in statistical and economic analysis, such as Laspeyres, Paasche, Fisher, and related index methods. Furthermore, the study discusses methodological issues associated with the use of index numbers, including changes in consumption patterns, the choice of comparison periods, and variations in the quality of goods and services. Such factors may influence the accuracy and reliability of measurement and therefore require careful statistical treatment. The work emphasizes that the usefulness and validity of index numbers depend heavily on the quality of available data and on the soundness of statistical procedures adopted during construction and estimation. The study highlights the value of index numbers as analytical instruments that support economic planning, policy formulation, and evaluation of economic performance. Overall, the study provides a theoretical and practical framework that assists students and researchers in understanding methods of measuring and analyzing economic change through statistical indicators.